Optimizing Alternative Funding Sources to Support School Quality: A Literatur Study - Sakhuroh Sakhuroh; Tuti Haryati; Sutrisno Sutrisno (FKIP - Universitas Riau, 2026)
Education financing plays a strategic role in improving school quality and supporting the sustainability of educational programs. However, many schools in Indonesia still depend heavily on government funding, limiting their ability to develop innovative and sustainable educational programs. Therefore, optimizing alternative funding sources has become an important strategy for improving school quality. This study aims to analyze the optimization of alternative education funding sources in supporting school quality through a literature study approach. The research employed a qualitative method using library research by examining 10 scientific articles, books, and educational policy documents published between 2020 and 2025. The selected literature focused on educational financing, alternative funding sources, financial management, and school quality improvement. Data were collected through systematic literature review techniques and analyzed using content analysis. The findings indicate that alternative funding sources, such as industry partnerships, community and alumni participation, school business units, and digital fundraising, contribute to improving educational facilities, teacher competencies, innovative learning programs, and school quality culture. Effective financial management, transparency, accountability, and school leadership also play important roles in optimizing educational financing and strengthening sustainable school quality improvement.